Personality and motivation matter in touring holidays: A preliminary investigation into heterogeneity among touring travelers - Gountas, J.; Dolnicar, S.; Gountas, Sandra (Cognizant Communication Corporation, 2011)
Touring travelers represent a significant market in Australia and are expected to play an even larger role in the future. Yet, to date, they are viewed and treated like one large homogeneous market. The aim of the present study was to question this assumption and investigate whether distinct segments exist among touring travelers. Results, based on an empirical study of 430 Australian travelers, indicate that at least two distinct segments can be constructed which differ in travel motivations, sociodemographics, and personality characteristics. These findings can be used to segment and harvest the market of tourist travelers through the development of targeted products and marketing messages.